PRODUCTION INFRASTRUCTURE OF VILLAGES OF SURKHANDARYA REGION - Mirzayev Khusniddin Kholmuminovich (American Journals Publishing, 2025)
The article analyzes the production infrastructure of the villages of Surkhandarya region, its condition and development prospects. The author studies the importance of the agricultural, industrial, transport and energy sectors in rural areas and makes proposals for increasing their efficiency. The article also covers the impact of the development of production infrastructure on employment, sources of income and economic well-being of the rural population. The results of the study include scientific and practical recommendations for the further development of production infrastructure in the region.
Keywords: Surkhandarya region, rural infrastructure, production sectors, agriculture, industry, transport, energy, economic development.